Exploring Undergraduate Biology Students’ Science Communication About COVID-19 - Couch, Brock; Wybren, Elizabeth; de Araujo Bryan, Mariana; Niravong, Thipphaphone; Jin, Ying; Bowen, Chloe; Barnes, M. Elizabeth (Frontiers in Education, 2022)
Effective science communication is important for mitigating the spread of COVID-19, but little is known about how college science students, who are the future of science, have communicated about COVID-19. In this study, we surveyed 538 biology students in the Southeastern United States about how they communicated about COVID-19 with others and how prepared they felt to communicate. We found that many students were communicating frequently but did not feel prepared to communicate accurately, particularly about vaccine safety and effectiveness. Students also wrote about their communication strategies, and many students reported using potentially ineffective communication. Finally, we explored student misconceptions about COVID-19 and found differences among religious, political, and racial/ethnic groups that could impact their communication to their communities about COVID-19. These results indicate a need for science communication education about COVID-19 among undergraduate scientists in training.